Strategic Approaches to Marketing Management in Contemporary Business Environments - Lestari, Vera (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to provide a comprehensive overview of strategic marketing management in contemporary business environments, focusing on the importance of customer-centric strategies, data-driven approaches to market segmentation, targeting, and positioning (STP), effective brand management, and the increasing significance of digital marketing. A thorough review of existing literature on strategic marketing management, including seminal works and recent research articles, was conducted to synthesize key insights and perspectives. The analysis encompassed various aspects such as customer-centricity, market segmentation, targeting, positioning, brand management, and digital marketing strategies. The findings highlight the evolving nature of marketing practices, driven by shifts in consumer behavior, technological advancements, and competitive dynamics. Key findings include the imperative of prioritizing customer-centricity, approaches to STP strategies, the importance of effective brand management in building strong brand equity, and the growing significance of digital marketing in reaching and engaging with target audiences. The implications of this study are manifold. For practitioners, the findings underscore the importance of aligning marketing strategies with evolving consumer needs and preferences, leveraging data analytics and technology to optimize marketing effectiveness, investing in effective brand management practices, and embracing digital marketing channels and technologies. From a theoretical standpoint, this study contributes to the existing body of knowledge by providing empirical evidence and insights into contemporary practices and challenges in strategic marketing management. It also highlights the need for interdisciplinary collaboration between scholars and practitioners to address complex marketing challenges and drive innovation in marketing practices.